2015
DOI: 10.1002/ece3.1584
|View full text |Cite
|
Sign up to set email alerts
|

Using sutures to attach miniature tracking tags to small bats for multimonth movement and behavioral studies

Abstract: Determining the detailed movements of individual animals often requires them to carry tracking devices, but tracking broad-scale movement of small bats (<30 g) has been limited by transmitter technology and long-term attachment methods. This limitation inhibits our understanding of bat dispersal and migration, particularly in the context of emerging conservation issues such as fatalities at wind turbines and diseases. We tested a novel method of attaching lightweight global positioning system (GPS) tags and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…A second solution will be to close the information gap about bat migration and other bat natural history using novel methods such as transmitter suturing developed by Castle, Weller, Cryan, Hein, and Schirmacher (2015) that has revealed long-distance movements of hoary bats (Weller et al, 2016). A third solution will be to integrate geographically extensive coordinated acoustic surveys into a conservation information system that draws on multiple lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A second solution will be to close the information gap about bat migration and other bat natural history using novel methods such as transmitter suturing developed by Castle, Weller, Cryan, Hein, and Schirmacher (2015) that has revealed long-distance movements of hoary bats (Weller et al, 2016). A third solution will be to integrate geographically extensive coordinated acoustic surveys into a conservation information system that draws on multiple lines of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Bats were released at the capture site after allowing them 20 minutes to recover from anesthesia. Bats to which tags were attached did not exhibit unusual levels of mass loss, skin irritation, or mobility while entering roosts 53 .…”
Section: Methodsmentioning
confidence: 99%
“…We attached tags to adult male hoary bats, which comprise >95% of captures at this site, selecting individuals with the highest mass captured on a given night. We attached tags to the dorsum, caudal to the scapulae and cranial to the pelvis using sutures following the methods of Castle et al 53 . Bats were released at the capture site after allowing them 20 minutes to recover from anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another alternative is radio‐tracking; however, a comprehensive review has found that most radio‐tracking devices used to study bats are too heavy, are being used with minimal ethical justification, and remain attached for an average of just 9 days (O'Mara et al, ). A more recent innovation for the use on small bats has been miniaturized GPS tags; however, currently this has only been successfully attempted with the use of anesthesia and sutures to attach the loggers—and battery life, tag weight and recapture rates remain ongoing issues (Castle, Weller, Cryan, Hein, & Schirmacher, ; Weller et al, ).…”
Section: Introductionmentioning
confidence: 99%